TEKNIK KONTROL SLIDING MODE UNTUK AUTOPILOT ROKET - Andiarti, Rika (Indonesian Journal of Aerospace, 2006)
This paper deals with autopilot for rocket tracking problem by using sliding mode controller. Rocket model is considered as a linear system with two control input; wing and tail deflection. Simulation results show that the controller effectively works and gives desired performance (fast reaching and low chattering).